Gross tumour delineation on computed tomography and positron emission tomography-computed tomography in oesophageal cancer: A nationwide study. (January 2019) - Nowee, M.E.; Voncken, F.E.M.; Kotte, A.N.T.J.; Goense, L.; van Rossum, P.S.N.; van Lier, A.L.H.M.W.; Heijmink, S.W.; Aleman, B.M.P.; Nijkamp, J.; Meijer, G.J.; Lips, I.M.; ,
Highlights: Interobserver variability in delineation of the oesophageal GTV can be considerable. Delineation variation is mainly located at the cranial and caudal border. PET significantly influences the delineated GTV in oesophageal cancer. The impact of PET to CT on observer variation of the GTV is limited. Accurate GTV delineation is essential for results of radiation boost-strategies. Abstract: Background and purpose: Accurate delineation of the primary tumour is vital to the success of radiotherapy and even more important for successful boost strategies, aiming for improved local control in oesophageal cancer patients. Therefore, the aim was to assess delineation variability of the gross tumour volume (GTV) between CT and combined PET-CT in oesophageal cancer patients in a multi-institutional study. Materials and methods: Twenty observers from 14 institutes delineated the primary tumour of 6 cases on CT and PET-CT fusion. The delineated volumes, generalized conformity index (CIgen) and standard deviation (SD) in position of the most cranial/caudal slice over the observers were evaluated. For the central delineated region, perpendicular distance between median surface GTV and each individual GTV was evaluated as in-slice SD. Results: After addition of PET, mean GTVs were significantly smaller in 3 cases and larger in 1 case. No difference in CIgen was observed (average 0.67 on CT, 0.69 on PET-CT). On CT cranial-caudal delineation variation ranged between 0.2 and 1.5 cm SD versus 0.2 and 1.3 cm SD on PET-CT. After addition of PET, the cranial and caudal variation was significantly reduced in 1 and 2 cases, respectively. The in-slice SD was on average 0.16 cm in both phases. Conclusion: In some cases considerable GTV delineation variability was observed at the cranial-caudal border. PET significantly influenced the delineated volume in four out of six cases, however its impact on observer variation was limited.